Sim-to-real transfer reinforcement learning for control of thermal effects of an atmospheric pressure plasma jet. (24th September 2019) - Witman, Matthew; Gidon, Dogan; Graves, David B; Smit, Berend; Mesbah, Ali
Abstract: Applications of atmospheric pressure plasma jets (APPJs) present challenging feedback control problems due to the complexity of the plasma-substrate interactions. The plasma treatment of complex substrates is particularly sensitive to changes in the physical, chemical, and electrical properties of the substrate, which may vary considerably within and between target substrates. The increasingly popular reinforcement learning (RL) methods hold promise for learning-based control of APPJ applications that involve treatment of complex substrates with time-varying or non-uniform characteristics. This paper demonstrates the use of a deep RL method for regulation of thermal properties of APPJs on substrates with different thermal and electrical characteristics. Using simulated data from an experimentally-validated, physics-based model of the thermal dynamics of the plasma-substrate interactions, an RL agent is trained to perform temperature setpoint tracking. It is shown that training the RL agent using a wide range of simulated thermal dynamics of the plasma-substrate interactions allows for capturing the diverse temperature responses of different substrates. Experimental demonstrations on a kHz-excited APPJ in He show that the proposed RL agent enables effective temperature control over a wide variety of substrates with drastically different thermal and electrical properties.